KONVERSI DAN DISKRIMINASI TERHADAP MUALAF DI DAERAH ISTIMEWA YOGYAKARTA (DIY) - Fatiyah Sudarmo (Balai Penelitian dan Pengembangan Agama Jakarta, 2019)
Abstract Freedom of religion and worship agreed in the constitution. The act of remembering and intolerance is not infrequently obtained, both from the nuclear family, the friendship environment, the workplace, and their social environment. This paper discusses to be analyzed and discussed about the discussion of the comparison (conversion) of mualaf both compile before reaching conversion of religion. And the forms or patterns of interaction carried out by the structure in the community of converts. Questions about intrinsic type research. Determination of participant purposive sampling. Data collected by in-depth interviews, observation, and documentation. Mailing lists and Huberman: (1) data reduction, (2) data presentation, and (3) drawing conclusions or verification. Based on the results of the study (1) the background of being an individual convert attended by informants namely spiritual emptiness, questioning the existence of God and distrust in the religion that was voiced, (2) responses from families that gave rise to conflicts related to coverage, truly, safely and smoothly the purpose those who are asked to return to their original religion, and to be ostracized, (3) there are those who argue from the social environment or the community, then turn into friendly.